(untitled) (Journal of the College of Education for Women, 2019)
The current study aimed at identifying the orientations of the female students of Faculty of Education for women in Baghdad University toward the different teaching methodologies and the differences in variable factor with different major, teaching phase and the interaction between them. The study sample consisted of (147) female students on whom a questionnaire composed of (36) items were applied after verifying its objective and steadiness. The results indicated that the orientations of the female students of Faculty of Education for Girls in Baghdad University toward the teaching methodologies are positive however it was negative toward the questionnaire. The results indicated also that there is difference in the orientation toward the methodology of delivering the lecture in favor of the computer’s division, however the orientation toward the second methodology (questionnaire methodology), was negative. The results indicated also that there are no differences between the variable factor of the division and the stage in the orientation toward the discussion but the interaction between them is considered as indicative. The orientation toward the fourth methodology (various teaching methodologies) for the variable factor of the teaching stage is indicative, however for the division and the interaction between them is non- Indicative. In the light of the results concluded by the study, the researcher recommended to improve the skills necessary for these methodologies and conduct another studies on the effects of other factors that have relationship with the orientations toward the teaching methodologies.